Book review: Forecasting and planning for volcanic hazards, risks, and disasters, by Paolo Papale (Ed.), 2020. Elsevier, London, 708 pages. Paperback: price $150.00, ISBN 9780128180822. - Scarpati, Claudio (Geologos, 2021)
Book review: Forecasting and planning for volcanic hazards, risks, and disasters, by Paolo Papale (Ed.), 2020. Elsevier, London, 708 pages. Paperback: price $150.00, ISBN 9780128180822